Education, Training, and Motivation Effects on Internal Auditor Performance - Matakupan, Suryana Salomi; Syarifuddin, Syarifuddin (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study examines the perceptions of internal auditors regarding the role of education, training, and work motivation in enhancing performance within the Kementerian Pekerjaan Umum. Using a qualitative descriptive approach, this research conducted in-depth interviews with internal auditors across different hierarchical levels and personnel management officials as a comparison and additional information. The findings reveal that education and training play a fundamental role in improving auditor performance, particularly given the technical nature of the ministry that requires dual competencies in both auditing and technical fields. Work motivation demonstrates complex multifaceted characteristics, encompassing both intrinsic motivations (professional responsibility, positive impact) and extrinsic motivations (compensation, supervisory recognition). The study identifies several challenges including material repetition in training programs for senior auditors, insufficient communication regarding specific training needs, and limited reward and punishment systems. These findings provide valuable insights for developing more effective human resource management strategies and supporting auditors to deliver better performance in government institutions.